Effect of intravaginal misoprostol use on uterine artery blood flow in patients with myoma uteri - Celik, H; Sapmaz, E; Serhatlioglu, S; Parmaksiz, C; Altingul, A (Elsevier Science Inc, 2003)
[Abstract Not Available]
Keywords: Myomectomy; Leiomyomas